Towards an Analysis of Compositional Strategies1 - Delalande, François (Circuit, 2007)
The author is interested in the process of composing, i.e. the invention of a piece of music from the initial spark of intuition to the final product. His study is based on the “Germinal” project, an experiment in composition involving fourteen composers working with identical technical resources in computer studio 123 of the grm (Groupes de recherches musicales) in Paris in 1985. Their creations all followed a common work schedule in four stages, with each composer adopting a very personal strategy at each of these stages. Describing their strategies amounts to giving an account not only of their actions, but also of the attitudes and decisions that led from an initial project to a final product. Four levels of criteria governing the decision-making process are then proposed: technical quality, grammaticality, the musical idea and the topic. The first two conform to a search for regularity while the latter two suggest a desire for singularity. These levels determine work attitudes in relation to sound and machines, i.e., poietic attitudes. From this comparative study several strategies have emerged, three of which are explained. Finally, the author develops the concept of singularity, which is a central concern of composers, and which may also be viewed as a challenge to computers and music analysis.